The effect of progestagens on immunological risk factors of preterm birth - N. N. Elizarova; N. V. Artymuk; E. G. Polenok (Фундаментальная и клиническая медицина)
Aim. To determine the level of IgA and IgG to estradiol, progesterone, and benzo[a]pyrene in women with or without preterm labor and to assess whether the administration of progestagens affect these parameters.Materials and Methods. We measured the levels of IgA and IgG to estradiol, progesterone, and benzo[a]pyrene in serum of 199 pregnant women (68 with PL and 81 with normal delivery) with the following analysis of associations between progestagen administration and these parameters.Results. The level of IgA to estradiol in patients with preterm labor was significantly higher than in women with normal delivery, and the administration of progestagens did not reduce their level in women with preterm birth.Conclusions. Measurement of the antibodies to estradiol may help in predicting pregnancy complications such as preterm birth.